Identifying Misconceptions Among Elementary School Teachers in Implementing the TaRL Approach and Differentiated Instruction - Candra Dewi Asih Pamungkas; Yunus Abidin; Dede Tri Kurniawan (MIMBAR PGSD Undiksha, 2026)
The implementation of the Merdeka Curriculum requires elementary school teachers to master the Teaching at the Right Level (TaRL) approach and differentiated instruction; however, classroom practices still reveal pedagogical ambiguities. This study aims to analyze and evaluate teachers’ misconceptions regarding these two approaches. A quantitative descriptive design was employed, involving 79 teachers as respondents. Data were collected using a diagnostic test instrument based on the Certainty Response Index (CRI) to identify teachers’ levels of understanding and confidence in the tested concepts, and were analyzed using descriptive quantitative techniques by categorizing responses into understanding, misconception, and lack of knowledge. The findings indicate that teachers experience significant misconceptions, particularly regarding the flexibility of student grouping in TaRL, which is often perceived as static classification, as well as conceptual overlap in process differentiation, where differentiated instruction is frequently misinterpreted as fully individualized teaching. Overall, teachers demonstrate adequate administrative understanding but encounter difficulties at the level of instructional implementation. This study concludes that teacher professional development programs need to shift from theoretical-administrative models toward practice-based clinical simulations, with implications for the importance of contextual and applicable training to bridge the gap between conceptual understanding and actual classroom practice.